Constructing Ni3C/2D g‐C3N4 Photocatalyst and the Internal Catalytic Mechanism Study. Issue 19 (6th August 2021) - Chen, Hanxiang; Yuan, Junjie; Yang, Wenshu; Yu, Yahui; Song, Yanhua; She, Yuanbin; Chen, Zhigang; Zhu, Xianglin; Li, Huaming; Xu, Hui
Abstract : Developing efficient, highly stable, and cheap photocatalysts are the keys to the industrial application of photocatalytic techniques. For the photocatalytic reactions, how to promote the separating of photogenerated carriers and construct active sites are crucial challenges. Herein, Ni3 C nanoparticles are loaded on 2D g‐C3 N4 as electron‐transferring centers. The mechanism of interface charge transfer in the photocatalytic reactions is studied. Benefited from the formed Schottky junction and the special activation effect of Ni3 C, Ni3 C/2D g‐C3 N4 owns better separation efficiency of carriers and more active sites to produce ⋅O2 − and ⋅OH species, which can enhance the photocatalytic activity. Finally, a highest rate of 90.3% for rhodamine B (Rh B) degradation is realized by the optimal proportion of Ni3 C/2D g‐C3 N4 . In addition, the increased photocurrent intensity and stronger signals of active species of Ni3 C/2D g‐C3 N4 indicate the dual functions of Ni3 C in both promoting the separation of carriers and the production of the active oxidation species. Abstract : Herein, NiC3 effectively boosts the photocatalytic performance of metal‐free semiconductor (2D g‐C3 N4 ). It exhibits excellent electrical conductivity and has the ability to export photogenerated electrons efficiently and participate in photocatalytic reaction.